2022
DOI: 10.1097/mou.0000000000001052
|View full text |Cite
|
Sign up to set email alerts
|

The ‘-ics’ of male reproduction: genomics, epigenetics, proteomics, metabolomics, and microbiomics

Abstract: Purpose of reviewTo review the most current findings, from the past 2 years, in various ‘-ics’ fields in male infertility, with a specific focus on nonobstructive azoospermia, the most severe form, and varicocele, the most common correctable cause of male infertility.Recent findingsRecent studies confirm previously identified causes and identify previously unknown genetic mutations as causes for nonobstructive azoospermia and varicocele.SummaryInfertility is a common problem for couples with approximately half… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…The next-generation omics advances (proteomics, transcriptomics, epigenomics, etc.) have begun to provide insight into understanding the pathophysiology of infertility associated with varicoceles [13]. These studies have identified numerous molecular changes in men with varicoceles, including regional hypomethylation or reduced expression of spermatogenesis-related proteins, which may reduce sperm viability and negatively impact fertility [14].…”
Section: Introductionmentioning
confidence: 99%
“…The next-generation omics advances (proteomics, transcriptomics, epigenomics, etc.) have begun to provide insight into understanding the pathophysiology of infertility associated with varicoceles [13]. These studies have identified numerous molecular changes in men with varicoceles, including regional hypomethylation or reduced expression of spermatogenesis-related proteins, which may reduce sperm viability and negatively impact fertility [14].…”
Section: Introductionmentioning
confidence: 99%